K-Politika a digital ethnographic study on the emergence of poltical activism in KS4GG Cebu's fandom network through their participatory culture - Gomez, Audrey Mae A.; Quilantang, Julia Ricci G.; Tañongon, Crina E.; Rosos, Daisy Mae M. (Cebu City College of Communication, Art, and Design , University of the Philippines Cebu, 2024)
The formation of K-pop Stans for Good Governance Cebu or KS4GG Cebu demonstrated how K-pop fandoms have evolved from simply admiring celebrities to actively advocating for social change. This study identified how the participatory culture among the fandom nodes under KS4GG Cebu propelled their political activism during the 2022 national elections. It is anchored on Henry Jenkins? (1992) concept of participatory culture and used social network analysis to (a) identify the relationships of the nodes, (b) examine the information flows between the nodes, (c) and analyze the structure and patterns that developed between the various network entities. Furthermore, conversation analysis revealed communication patterns within the network, including who communicates with whom and the frequency of their conversations. Results obtained indicate that KS4GG Cebu is a closed social network composed of both centralized and decentralized subnetworks that interact on Facebook. Even with its closed nature, the network grew with increased community awareness and interactions among nodes. However, the incorporation of K-pop into political discourse has made politicians more like celebrities, blurring the line between entertainment and politics. Despite such, combining K?pop with politics has engaged fans in both pop culture and politics.
Thesis (Bachelor of Arts in Communication)--UP Cebu, May 2024.
Includes bibliographical references and appendices.